Breast cancer in the State of Piauí, Northeastern Brazil: from diagnosis to treatment (Research, Society and Development, 2023)
Breast cancer is the most common type of cancer in women worldwide, when non-melanoma skin cancers are excluded, accounting for more than 2 million new cases each year and being the leading cause of mortality in women from all over the world. Delay in starting treatment is related to a worse prognosis. In Brazil, law nº 12.732 of November 22, 2012 provides for a period of 60 days from the diagnosis to start treatment for neoplasms. Thus, the objective of this study was to discuss the epidemiology of breast cancer in the state of Piauí, from its diagnosis to the beginning of treatment in the Sistema Único de Saúde (SUS) network. The method used for the study was a retrospective analysis with a descriptive quantitative cross-sectional approach. Data collection took place between August 2022 and March 2023, using the Sistema Único de Saúde Database (DATASUS). The results obtained showed failure to carry out an early diagnosis, underutilization of the therapeutic modalities offered, in addition to the delay between diagnosis and the beginning of treatment.